SQL injection attacks and defense - Clarke, Justin (Elsevier, 2012)
SQL injection represents one of the most dangerous and well-known, yet misunderstood, security vulnerabilities on the Internet, largely because there is no central repository of information available for penetration testers, IT security consultants and practitioners, and web/software developers to turn to for help. SQL Injection Attacks and Defense, Second Edition is the only book devoted exclusively to this long-established but recently growing threat. This is the definitive resource for understanding, finding, exploiting, and defending against this increasingly popular and particularly destructive type of Internet-based attack. SQL Injection Attacks and Defense, Second Edition includes all the currently known information about these attacks and significant insight from its team of SQL injection experts, who tell you about: Understanding SQL Injection -- understand what it is and how it works; Find, confirm and automate SQL injection discovery; Tips and tricks for finding SQL injection within code; Create exploits for using SQL injection; Design apps to avoid the dangers of these attacks; SQL injection on different databases; SQL injection on different technologies; SQL injection testing techniques; Case Studies. Covers unique, publicly unavailable information, by technical experts in such areas as Oracle, Microsoft SQL Server, and MySQL -- including new developments for Microsoft SQL Server 2012 (Denali). Written by an established expert, author, and speaker in the field, with contributions from a team of equally renowned creators of SQL injection tools, applications, and educational materials.